2018
DOI: 10.1177/0095798418764244
|View full text |Cite
|
Sign up to set email alerts
|

Gender Typicality, Felt Pressure for Gender Conformity, Racial Centrality, and Self-Esteem in African American Adolescents

Abstract: Using a sample of 203 African American late adolescents aged 16 to 19 years (M age = 17.77 years), we examined whether two aspects of gender identity-gender typicality and felt pressure for gender conformity-were related to self-esteem. Racial centrality (i.e., the importance of race to the individual's self-concept) and gender were tested as moderators of these relations. Compared to girls, boys reported that they were more typical of their gender group (i.e., gender typicality) and that they experienced grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
(125 reference statements)
1
11
0
1
Order By: Relevance
“…We chose these constructs because of their established relations to well‐being. Higher levels of gender typicality are associated with lower levels of psychopathology, positive psychosocial adjustment, and greater academic motivation in adolescent and young adult racially/ethnically diverse samples (DiDonato & Berenbaum, ; Jewell & Brown, ; Skinner, Kurtz‐Costes, Wood, & Rowley, ; Smith & Leaper, ; Vantieghem, Vermeersch, & Van Houtte, ). In contrast, higher levels of felt pressure in preadolescents and adolescents are associated with lower levels of psychosocial adjustment (Corby, Hodges, & Perry, ; Yunger, Carver, & Perry, ).…”
Section: Gender Identity Development During Adolescencementioning
confidence: 99%
“…We chose these constructs because of their established relations to well‐being. Higher levels of gender typicality are associated with lower levels of psychopathology, positive psychosocial adjustment, and greater academic motivation in adolescent and young adult racially/ethnically diverse samples (DiDonato & Berenbaum, ; Jewell & Brown, ; Skinner, Kurtz‐Costes, Wood, & Rowley, ; Smith & Leaper, ; Vantieghem, Vermeersch, & Van Houtte, ). In contrast, higher levels of felt pressure in preadolescents and adolescents are associated with lower levels of psychosocial adjustment (Corby, Hodges, & Perry, ; Yunger, Carver, & Perry, ).…”
Section: Gender Identity Development During Adolescencementioning
confidence: 99%
“…Thus far, gender research seems to have been developing in two mostly independent research areas: One area looks at a multidimensional gender identity consisting of several factors and takes place mostly in psychological development research (Ruble et al, 2006;Steensma et al, 2013;Roberts and Fantz, 2014;Perry et al, 2019). Another area emerges primarily from queer and health research and looks at non-binary gender identities mostly focused on trans identities (Butler, 2009;Westbrook and Saperstein, 2015;Skinner et al, 2018;Poteat et al, 2019), although methodology and research contents on non-binary adolescents are still limited (Scandurra et al, 2019).…”
Section: Identifying Gender Identity Empiricallymentioning
confidence: 99%
“…Past research has found stricter gender roles for male than for female children (Blakemore 2003;Skočajić et al 2019;Wilbourn and Kee 2010). Studies on gender differences in felt pressure to conform have consistently reported that males feel greater pressure to conform to the male gender role than females with respect to the female gender role, both in childhood and in adolescence (Aoyagi et al 2018;Egan and Perry 2001;Hoffman et al 2019;Skinner et al 2018;Vantieghem and Van Houtte 2015;Yunger et al 2004).…”
Section: The Role Of Pressure For Gender Conformitymentioning
confidence: 99%